Ultrasound-assisted extraction of antioxidants in Misai Kucing (Orthosiphon stamineus) - Ho, Swee Kheng; Tan, Chin Ping; Thoo, Yin Yin; Abas, Faridah; Ho, Chun Wai (MDPI, 2014)
Ultrasound-assisted extraction (UAE) with ethanol was used to extract the compounds responsible for the antioxidant activities of Misai Kucing (Orthosiphon stamineus). Response surface methodology (RSM) was used to optimize four independent variables: ethanol concentration (%), amplitude (%), duty cycle (W/s) and extraction time (min). Antioxidant compounds were determined by total phenolic content and total flavonoid content to be 1.4 g gallic acid equivalent/100 g DW and 45 g catechin equivalent/100 g DW, respectively. Antioxidant activities were evaluated using the 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) radical scavenging capacity assay and the 2,2-diphenyl-1-picrylhydrazyl (DPPH•) radical scavenging capacity assay to be 1,961.3 and 2,423.3 µmol Trolox Equivalent Antioxidant Capacity (TEAC)/100 g DW, respectively. Based on the optimal conditions, experimental values were reported to be close to the predicted value by RSM modeling (p > 0.05), indicating the suitability of UAE for extracting the antioxidants of Misai Kucing. Rosmarinic acid, kaempferol-rutinoside and sinesetine were identified by high performance liquid chromatography-mass spectrometry.